1985
DOI: 10.1051/agro:19850707
|View full text |Cite
|
Sign up to set email alerts
|

Antagonisme in vitro de Trichoderma spp. vis-à-vis de Rhizoctonia solani Kühn

Abstract: Pour Trichoderma, dont la systématique est assez aléatoire, les modes d'action antagoniste, bien étudiés par DE NNI S & WE BSTER (1971, a, b, c) peuvent servir

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
3

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 1 publication
0
19
0
3
Order By: Relevance
“…Competitiveness of Trichoderma spp. based on rapid growth and germination is a decisive feature for antagonism (Camporota, 1985;Chet et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Competitiveness of Trichoderma spp. based on rapid growth and germination is a decisive feature for antagonism (Camporota, 1985;Chet et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Both the dual and alone cultures were incubated at 25°c for four days, and measurement of radial mycelia of the fungus was taken every 24 hours. The percentage inhibition of growth (I) (Azza and Allam, 2004;Camporota, 1985;Carl and al., 2005;Rapilly, 1968). Effect of the volatile substances of Trichoderma harzianum on the growth of the pathogenic fungi on the PDA medium (remote confrontation): This method consists in mending the antagonist fungus and the pathogenic one, in two plates separated thereafter, an assembly is carried out by the superposition of two plates, antagonist in bottom and the pathogenic one in top, the junction between the two plates is ensured by layers of parafilm in order to avoid all loss of volatile substances.…”
Section: Methodsmentioning
confidence: 99%
“…Both the dual and the alone cultures were incubated at 25°c,in the darkness for four days, and measurement of radial mycelia growth were taken every 24 hours. The percentage growth inhibition (I) was calculated like previously (Camporota, 1985;Fadwa and al., 2009) The antagonistic capability in vitro of Trichoderma harzianum against the pathogenic fungus: The results showed that: 1-The direct confrontation of Trichoderma harzianum against the different fungal isolates in vitro on PDA medium, showed that when the mycelium of both the cultures came in contact with each other the hyphal growth of the pathogenic fungus were found to be inhibited by the hyphae of Trichoderma harzianum.This inhibition with different ratios, it was equal in the fourth day of the experiment to 23% , 26.66% and 40%for Alternaria alternata1, Alternaria alternata2 and Alternaria infectoria, respectively, but amounted a lowest ratio in the fourth day to 6.66% for Fusarium acuminatum . [ Table (2) and figures (3), (4-1A),(4-2A),(4-3A)and (4-4A)].…”
Section: Methodsmentioning
confidence: 99%
“…Both the dual and alone cultures were incubated at 25°c for four days, and measurement of radial mycelia of the fungus were taken every 24 hours. The percentage growth inhibition ( I ) was calculated using the formula given [1], [22], [10], [11].…”
mentioning
confidence: 99%